Ameliorative potential of gallic acid on the activation of ROS and down-regulation of antioxidant enzymes in cardiac tissue of rats infused with advanced glycation end products - S. Umadevi, V. Gopi, A. Parthasarathy, V. Elangovan (Journal of Applied Pharmaceutical Science)
Advanced glycation end-products (AGEs) are implicated in the pathogenesis of diabetic complications including cardiac dysfunction and heart failure. We aimed to investigate the effects of circulatory AGEs on the oxidative stress parameters in the rat hearts, and also to examine the protective role of gallic acid (GA) in attenuating the AGEs-induced oxidative stress. The experimental Wistar rats were infused with in vitro synthesized rat serum albuminderived AGEs intravenously at a dose of 50mg/kg/day, for 30 days with or without GA. The control animals received equal amount of unmodified rat serum albumin (RSA) intravenously for 30 days. The rats treated with AGEs alone exhibited increased plasma levels of creatine kinase (CK) (p
Keywords: Advanced glycation end products, oxidative stress, antioxidant enzymes, gallic acid.